Development of numerical tools to aid the design of complex geometry profile extrusion dies - Gonçalves, N. D. (2011)
The research team of this work is involved since the mid-nineties on the development of computational tools to aid the design of profile extrusion dies. Initially, the numerical code employed was based on structured meshes that limited its application to simple geometries. The work planned in this PhD programme comprises the development of a numerical modelling code able to deal with unstructured meshes and its application on the design of profile extrusion dies comprising complex cross sections. In its current state the numerical code under development is able to model de flow of generalized Newtonian fluids inside flow channels using unstructured meshes. This paper describes briefly the current state of the developed code and illustrates its application in a case study involving the design of a profile extrusion die comprising a complex cross section.